Ultrasonic Cleaning of The Oral Cavity in Senile People - Rasulova Makhpiratkhon Mehmonkulovna (Scientific Trends, 2023)
The aim of this study was to evaluate the effectiveness of carers’ education on improvements in oral health and denture hygiene of care-dependent and cognitively impaired older people in nursing homes compared to those without intervention. Carers’ education improves oral health of people in nursing homes over a clinically relevant period of time. Implementation of ultrasound baths is a simple and effective measure to improve denture hygiene of both institutionalized elderly people and seniors with dementia and in severe need of care. From a clinical standpoint, it is noteworthy that the respective interventions can be easily implemented in everyday care routine.
Keywords: oral health, intervention, older people, nursing home, longitudinal.